Perception on Evaluation of Teaching Effectiveness: A Case of School of Medicine and Health Sciences of Kenya Methodist University. - Clive, Obare Mose; Nyangena, Elijah (International Journal of Nursing Education)
Effective teaching is an art that should be judged based on the performance of the graduates program and achievement of curriculum outcomes. However, teaching is a complex and demanding activity that involves mastery of content, classroom control, techniques of organization, and command of teaching skills. The purpose of this study was to determine the effectiveness of teaching in the undergraduate degree programs in the School of Medicine and Health Sciences at the Kenya Methodist University (KeMU) main campus. This study focused on the full time face to face mode of instruction. A descriptive cross-sectional design and questionnaire were used. The sample was a total of 18 lecturers and 80 full time students in the School of Medicine and Health Sciences representing 4 different programs. An interview guide was designed to elicit views from the Chairmen of 4 Departments (CoD) in the School of Medicine and Health Sciences with full time students and Director of Quality Assurance and standards (DQA) regarding the teaching and learning process in the School. The findings showed that 89% of the lecturers stated that they demonstrated mastery of content compared to 49% of the students. The findings also indicated that teaching evaluation was viewed as a means to facilitate improvement within medical education. On the other hand 72% of the lectures appreciated that evaluation of their teaching effectiveness improved their performance and teaching skills. Thus teaching quality education was believed to be dependent on content, process, teacher and student characteristics as well as learning outcome, with an emphasis on the latter.